Die Legende im literarischen Schaffen Gustave Flauberts und Joseph Roths - Birk, Matjaž (Primerjalna književnost, 2006)
A legend in the literary work of Gustav Flaubert and Joseph Roth. The article discusses the characteristics of the actualisation of a legend as a literary form in Gustav Flaubert's story The Legend of Saint Julian the Hospitaller (1877) and in Joseph Roth's novel Tarabas (1934). The two authors used the genre characteristics of a legend combined with elements of fairy tale and mythical story-telling, intertwining them according to construction and deconstruction principles in the manner of parody and the grotesque. Both actualisations of legends are aesthetic attempts to go beyond the spiritual and ideological symptoms of the historical moment in which they appear.
Keywords: Flaubert, Gustave, 1821-1880; Roth, Joseph, 1894-1939; avstrijska književnost; francoska književnost; French literature; history of literature; literarna zgodovina; comparative literature; primerjalna književnost; literarni vplivi; legende; pravljice